Determination of Relative Reactivity of HSAB Complexes Using DFT Theory - Humadi, Salah Aldin (Iraqi Journal of Science, 2023)
Based on the density functional theory (DFT) , the stability of molecular complexes has been predicted according to hard-soft acid base (HSAB) theory. Relative stability of products and reactivity of soft base sulfide derivatives with halogens (Iodine , Bromine , Chlorine) as soft acid was studied to determine the relative ability of these reactants causing the reaction to be more spontaneous.DFT at the levels of B3LYP/3-21G and B3LYP/3-21G (d) was used to study HOMO LUMO energy gaps , bonds length and total energy to calculate the softness sequence of each type of acid or base mentioned in this work. All cases studied prove that iodine can be considered as the most softness acid and ethyl methyl sulfide≈ dimethyl sulfide the most softness bas